How does search engine advertising work and why is it so important to get it right? - Brigden, Jim (Henry Stewart Talks, 2009)
Online advertising spend, The power of search engine advertising, Buying behavior, Advertising through paid results, Elements of success, Appearing in natural results, How do you get listed?, Improve relevance, Improve popularity, Why it is important to get it right
Archived at 2022/04/11